Violence and non-violence in Daniel - Venter, P. M. (Old Testament essays, 2001)
When reading the apocalyptical text of Daniel with attentiveness to the politics of rhetoric as text expressing a political theology, the reader is confronted with the seemingly contradiction that narratives with violent language are used to persuade readers to act non-violently in a crisis. This problem is discussed by first paying attention to the way violence is depicted in the book of Daniel and, second, by studying the expectation the book has of its readers. An answer is proposed from a theological angle indicating the sufficiency of God's violence.